Neoproterozoic to early Cambrian small shelly fossil assemblages and a revised biostratigraphic correlation of the Yangtze Platform (China) - Steiner, Michael; Li, Guoxiang; Qian, Yi; Zhu, Maoyan; Erdtmann, Bernd-Dietrich (Palaeogeography, Palaeoclimatology, Palaeoecology, 2007)
Small shelly fossils (SSFs) occur widely on the Yangtze Platform and have great potential for biostratigraphic subdivision of pre-trilobitic Early Cambrian strata. Based on the SSF record of the shallow water realm, five biozones can be recognized for the Meishucunian Stage. In ascending order the biozones are: Anabarites trisulcatus-Protohertzina anabarica Assemblage Zone; Paragloborilus subglobosus-Purella squamulosa Assemblage Zone; Watsonella crosbyi Assemblage Zone (formerly Heraulti-pegma yunnanensis Zone); poorly fossiliferous interzone; Sinosachites flabelliformis-Tannuolina zhangwentangi Assemblage Zone. In addition one SSF biozone is recognized for the overlying Qiongzhusian Stage: Pelagiella subangulata Taxon-range Zone. The formerly used Siphogonuchites triangularis-Paragloborilus subglobosus Zone and Heraultipegma yunnanensis Zone are discussed and redefined. Approximately 80 species of SSFs were screened for their spatial and temporal distribution on the Yangtze Platform. Variations in lithofacies and biofacies can be recognized throughout the Yangtze Platform, extending over an area of 2000 x 900 km. In a deeper water shelf setting the first zone is represented by the Protohertzina anabarica-Kaiyangites novilis Assemblage Zone, while younger zones are not recognized in the southern region. At the northern platform margin the Qiongzhusian is represented by the Ninella tarimensis-Cambroclavus fangxianensis Assemblage Zone and the Rhombocorniculum cancellatum Taxon-range Zone. The southeastern Shaanxi-western Hubei region followed a slightly different lithological and faunal development than the rest of Yangtze Platform, indicating a stronger similarity with parts of East Gondwana. Some taxa such as W crosbyi, P. subangulata, R. cancellatum, Microdictyon effusum, A. trisulcatus, Protohertzina unguliformis, and P anabarica occur nearly worldwide and support an international correlation of Early Cambrian sequences between the Yangtze Platform and smaller West Gondwanan blocks, Siberia, Newfoundland, ...